Improving the light output power of DUV-LED by introducing an intrinsic last quantum barrier interlayer on the high-quality AlN template. (December 2017) - Tsai, Chia-Lung; Liu, Hsueh-Hsing; Chen, Jun-Wei; Lu, Chien-Pin; Ikenaga, Kazutada; Tabuchi, Toshiya; Matsumoto, Koh; Fu, Yi-Keng
Abstract: We demonstrate that the light output power of deep ultraviolet light-emitting diodes (DUV-LEDs) can be improved by introducing an intrinsic last quantum barrier interlayer to a high quality AlN template. The light output power of the DUV-LEDs can be doubled by substituting the last quantum barrier with an intrinsic last quantum barrier (u-LQB)/Mg-doped LQB for only pure u-LQB in the same thickness with a 35 A/cm 2 injection current. It is believed that the improved performance of the DUV LED could be attributed to the decreased diffusion of Mg tunneling into MQW and the reduction of sub-band parasitic emissions.